1999
DOI: 10.1023/a:1008627824731
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Compliance is a well recognised but still unresolved health problem; improvement of compliance to treatment would increase cost-effectiveness. One of the current methods used to measure treatment compliance in a clinical drug trial is through the use of a patient diary. In order to interpret data in these diaries it is important to also assess how compliant patients are in completing diaries. Patient compliance of standard diary completion was measured in 69 patients with perennial rhinitis, who were randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…All study patients had access to a psychiatrist and were taking medication. Furthermore, the very process of daily recording may improve medication adherence (van Berge Henegouwen et al 1999 ). In clinical practice, most patients would not volunteer to keep a long-term daily record.…”
Section: Discussionmentioning
confidence: 99%
“…All study patients had access to a psychiatrist and were taking medication. Furthermore, the very process of daily recording may improve medication adherence (van Berge Henegouwen et al 1999 ). In clinical practice, most patients would not volunteer to keep a long-term daily record.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other ongoing tests of wearable sensors in Parkinson’s patients which are observational [ 8 ], the PD Manager pilot will use a randomised controlled design. The most common traditional way of gathering information on symptoms from patients is through patient diaries [ 9 ]. This pilot study will therefore use symptom diaries as a comparator to the automated and electronic PD_Manager system for informing patient care and treatment plans.…”
Section: Introductionmentioning
confidence: 99%
“…The reminder diary was drawn up in consultation with the staff of the hypertension clinic and a perusal of the literature. 16 , 17 The diary consisted of. simple basic information on hypertension with a new fact presented for reading on each consecutive day; suggestions for specific progressive exercises to do each day which were explained during the monthly telephone calls; 23 reminders on what to eat and what not to eat (informed by the dietician in the clinic according to the Gauteng Department of Health healthy eating plan 24 ); and a question on whether medication had been taken for that day.…”
Section: Research Methods and Designmentioning
confidence: 99%
“…Reminder diaries may be an intervention that improves adherence to lifestyle modification, 16 , 17 as they are visible reminders that can be reviewed by health care professionals during clinic visits and may motivate patients. Arrigo et al showed that, in patients one year post-cardiac rehabilitation, using a diary and three-monthly group education sessions almost doubled patients’ adherence to exercise compared with patients who did not receive the diary or group sessions.…”
Section: Introductionmentioning
confidence: 99%